Grazing Effects on the Easily Measurable Plant Functional Traits of Quercus semecarpifolia Sm. Seedlings - Dorji, Tshewang; Gyaltshen, Dorji; Ghemiray, Damber Kr.; Wangda, Pema; Fukuda, Kenji (Indian Forester, 2015)
In a temperate broadleaf forest of Western Bhutan dominated by old growth brown oak (Quercus semicarpifolia sm.) with a history of overgrazing, we aimed to study the grazing response of oak seedlings by comparing grazed and ungrazed seedlings based on some easily measurable plant functional traits such as plant height, leaf area and leaf mass area ratios (LMA). Our study found that grazing was strongly associated with shorter plant height, thicker leaves, smaller leaf area and high leaf mass per area ratios (LMA) of Quercus semecarpifolia seedlings. Seedling collar diameter increment was not affected by grazing. LMA was found to be the best plant trait that could optimally predict the grazing response on plant growth. Shorter plant height, higher LMA and leaf thickness coupled with presence of more surface spines in the leaves of grazed plants could be some forms of grazing resistance or herbivory tolerance rather than adaptations to survive repeated herbivory. The study concludes that higher LMA values do not necessarily be limited to plants of nutrient poor sites or those growing under climatic stresses as generally assumed but are also attributed by anthropogenic activities like overgrazing.